Pelayanan Prima pada Nasabah Lansia di Bank 9 Jambi - Mursal, M; Sipuldi, S; Fauzi, Muhammad; Alparedi, Topan; Syarif, Defiar (Jurnal Informatika Ekonomi Bisnis, 2021)
Excellent service is the main thing that must always innovate in meeting customer needs. In the competitive banking world, direct contact with service is very important because customer satisfaction is a reflection of the quality of service. This study describes excellent service to the elderly who have several obstacles such as hearing loss, low education levels, communication barriers, which must receive special attention in service. The method in this study uses a descriptive qualitative type, then the results of the study show that excellent service has been implemented for the elderly with various strategies that have been implemented such as using regional languages for elderly customers who have problems understanding banking terms in transactions.